Remote education and student learning in times of Covid-19: the speech of teachers of a teaching institution in the state of Paraná (Research, Society and Development, 2022)
This article had as general objective to analyze the perception of a group of teachers from Elementary and High School of an educational institution in the state of Paraná about the learning process of students during remote teaching that took place in the Covid-19 pandemic. The methodology was qualitative, of the case study type. Data collection took place through a questionnaire with 15 elementary and high school teachers from an institution in the Paraná State Network, in order to verify the teacher profile and perception of the remote teaching process. For data analysis, we used the Collective Subject Discourse (DSC) technique, with the central ideas presented in the category: remote teaching and the students' learning process. The results showed that government actions (creation of Aula Paraná, use of Google Classroom, Business Intelligence) facilitated learning, but this was not effective for all students due to lack of equipment, internet or difficulty in adapting.